Imagining and tinkering with assistive robotics in care for the disabled - Mossfeldt Nickelsen Niels Christian (Paladyn, 2019)
The media and political-managerial levels focus on the opportunities to re-perform the Scandinavian welfare states through digitization. Especially in Denmark, this trend is prominent. Welfare technology is a Scandinavian notion used to point at assistive technologies intending to support the elderly, the disabled and care providers. Feeding assistive robotics (FAR) is a welfare technology relevant to citizens with no or low function in their arms. Despite national dissemination strategies, it proves difficult to recruit suitable users. There have been many promises for the potential of assistive robotics including more cost-efficient healthcare delivery, engaged patients and connected care providers. However, the realities of enacting assistive robotics, whether as patients or care providers, can be complicated in ways often unanticipated by government agencies and technology developers. This study discusses governmental agencies’ and technology developers’ visions with regard to what robotics may do and argues that these visions intertwine with affected stakeholders’ organizing of theirworlds. On this founding, the article discusses the resulting tinkering during implementation. The study exemplifies and demonstrates how ethnography can be used as an important method in Human Robot Interaction (HRI) research. The Actor Network Theory idea of ‘follow the actor’ inspired the study that took place as multi-sited ethnography at different locations in Denmark and Sweden. Based on desk research, observation of meals and interviews the study examines sociotechnical imaginaries and their practical and ethical implications.Human and FAR interaction demands engagement, sustained patience and understanding of the citizen’s particular body, identity and situation. The article contributes to the HRI literature by providing detailed empirical analysis based on an ethnographic studywhere political strategies, technology developers’ assumptions and affected stakeholders’ everyday hassles are in focus at the same time.